2022
DOI: 10.3390/jvd1010003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Associated with Type 2 Diabetes Mellitus Complications over Time: A Literature Review

Abstract: Early detection of type 2 diabetes mellitus (T2DM) complications is essential to prevent disability and death. Risk prediction models are tools to estimate the probability that an individual with specific risk factors will develop a future condition within a certain time period. A predictive model that incorporates time to quantify the risk of T2DM complications such as cardiovascular diseases (CVD) event is still lacking. Well-established and validated predictive models of T2D complications are vital to strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Unlike T1DM, T2DM can be prevented by maintaining a healthy lifestyle that involves regular exercise, smoking cessation, a healthy diet and reversing obesity [8,56,57]. On the other hand, individuals with T2DM are believed to have a higher risk of several complications including stroke, ischemic heart diseases [5], chronic kidney disease [58,59] and increased hospitalization.…”
Section: Type 2 Dmmentioning
confidence: 99%
“…Unlike T1DM, T2DM can be prevented by maintaining a healthy lifestyle that involves regular exercise, smoking cessation, a healthy diet and reversing obesity [8,56,57]. On the other hand, individuals with T2DM are believed to have a higher risk of several complications including stroke, ischemic heart diseases [5], chronic kidney disease [58,59] and increased hospitalization.…”
Section: Type 2 Dmmentioning
confidence: 99%
“…A previous study demonstrated that patients with type 2 DM often have relatively impaired genetic function, and genome instability is believed to be a factor that contributes to type 2 DM 3 10 . Type 2 DM patients are more likely to develop various conditions that affect elderly people, causing type 2 DM to be one of the world's most major health problems 11 – 20 . Tissue damage and multiorgan dysfunction, such as cardiovascular disease, stroke, foot ulcers, chronic kidney failure, and diabetic retinopathy, can occur in type 2 DM patients 21 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, an estimated 537 million people are at an increased risk of type 2 DM, and this number is expected to increase to 592 million by 2035 and reach 783 million by 2045 1,2 . Type 2 DM patients can develop various complications, including cardiovascular disease, stroke, foot ulcers, chronic kidney failure, and diabetic retinopathy, 3–10 making it one of the world's most critical health concerns 11,12 . Type 2 DM is a multifactorial condition characterized by high blood glucose levels (hyperglycemia), 13–15 which are influenced by genetic and epigenetic factors 16–19 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Type 2 DM patients can develop various complications, including cardiovascular disease, stroke, foot ulcers, chronic kidney failure, and diabetic retinopathy, 3-10 making it one of the world's most critical health concerns. 11,12 Type 2 DM is a multifactorial condition characterized by high blood glucose levels (hyperglycemia), [13][14][15] which are influenced by genetic and epigenetic factors. [16][17][18][19] DNA methylation, an epigenetic event commonly found in elderly individuals, exhibits changes in type 2 DM patients and correlates with poor health status in humans.…”
mentioning
confidence: 99%